The Authoritative Style as an Effective Approach to Fostering Discipline among Tahfidz Students at Pesantren Kyai Syarifuddin Lumajang - Amanah, Luluk Ma’rifatul (Pesantren and Community Development Studies - Islamic Institute of Syarifuddin, Indonesia., 2024)
Pesantren play a strategic role in shaping students' character, particularly in fostering discipline among tahfidz (Qur’an memorization) students. One of the prominent caregiving approaches applied in the pesantren environment is the authoritative style, which combines firmness with warmth. This approach is considered effective in building discipline because it provides room for dialogue and responsible freedom for students. This article presents findings from a qualitative research study conducted at Pesantren Kyai Syarifuddin, Lumajang. The results reveal that the application of the authoritative technique by teachers positively contributes to improving the discipline of tahfidz students. Supporting factors include students’ internal motivation, effective communication between teachers and students, and parental support. The impacts of this approach are reflected in students’ increased active participation in learning activities, enhanced discipline, and the growth of stronger learning motivation. The study concludes that the authoritative approach is proven effective in fostering discipline and consistency among tahfidz students in the Qur’an memorization process, while also strengthening independent and responsible character development.